Girl, interrupted - Goldberg, Whoopi, 1950-; Jolie, Angelina, 1975-; Kaysen, Susanna, 1948-; Konrad, Cathy; Loomer, Lisa.; Mangold, James; Phelan, Anna Hamilton; Redgrave, Vanessa, 1937-; Ryder, Winona, 1971-; Wick, Douglas; Wick, Douglas; Columbia Pictures; et al. (Culver City, Calif. : Columbia Pictures : Sony Pictures Home Entertainment, 2004)
La fascinante historia real de la vida alterada de una mujer joven que permanece en un famoso hospital psiquiátrico a finales de los 60's.
Based on the book by Susanna Kaysen.
DISPONIBLE
Features include: theatrical trailers ; director's commentary ; deleted scenes with commentary ; The making of Girl interrupted ; isolated music score ; talent files ; production notes.
Videodisc release of a 1999 motion picture.
Director of photography, Jack Green ; music, Mychael Danna.
Winona Ryder, Angelina Jolie, Whoopi Goldberg, Vanessa Redgrave.
Keywords: Kaysen, Susanna, -- 1948- -- Salud mental; Enfermos mentales; Hospitales psiquiatricos; Psicoterapia